Contrasting current challenges from the Brazilian and Canadian national health systems: The Besrour Papers: a series on the state of family medicine in Canada and Brazil - Ponka, David (Can Fam Physician, 2019)
OBJECTIVE: To compare the national health systems of Canada and Brazil and how both countries have addressed similar challenges in their primary care sectors. COMPOSITION OF THE COMMITTEE: A subgroup of the Besrour Centre of the College of Family Physicians of Canada developed connections with colleagues in Brazil and collaborated to undertake a between-country comparison, comparing and contrasting various elements of both countries’ efforts to strengthen primary care over the past few decades. METHODS: Following a literature review, the authors collectively reflected on their experiences in an attempt to explore the past and current state of family medicine in Canada and Brazil. REPORT: The Brazilian and Canadian primary care systems are faced with similar challenges, including geography, demographic changes, population health inequities, and gaps in universal access to comprehensive primary care services. Although the approaches to addressing these challenges are different in both settings, they highlight the central importance of family physicians in both systems. Both countries continue to face considerable challenges in the context of mental health services in primary care. It remains important for Canada to draw lessons from the primary care systems and reforms of other countries, such as Brazil.